Design of Low Bandgap CsPb1−xSnxI2Br Perovskite Solar Cells with Excellent Phase Stability. Issue 30 (23rd June 2021) - Chen, Gangshu; Li, Pengwei; Xue, Tangyue; Su, Meng; Ma, Junjie; Zhang, Yiqiang; Wu, Tianhao; Han, Liyuan; Aldamasy, Mahmoud; Li, Meng; Li, Zehua; Ma, Jiale; et al.
Abstract: Novel all‐inorganic Sn‐Pb alloyed perovskites are developed aiming for low toxicity, low bandgap, and long‐term stability. Among them, CsPb1− x Sn x I2 Br is predicted as an ideal perovskite with favorable band gap, but previously is demonstrated unable to convert to perovskite phase by thermal annealing. In this report, a series of CsPb1− x Sn x I2 Br perovskites with tunable bandgaps from 1.92 to 1.38 eV are successfully prepared for the first time via low annealing temperature (60 °C). Compared to the pure CsPbI2 Br, these Sn‐Pb alloyed perovskites show superior stability. Furthermore, a novel α‐phase‐stabilization mechanism of the inorganic Sn‐Pb alloyed perovskite by reconfiguring the perovskite crystallization process with chloride doping is provided. Simultaneously, a dense protection layer is formed by the coordination reaction between the surface lead dangling bonds and sulfate ion to retard the permeation of external oxygen and moisture, leading to less oxidation of Sn 2+ in perovskite film. As a result, the fabricated all‐inorganic Sn‐Pb perovskite solar cells (PSCs) show a champion power conversion efficiency of 10.39% with improved phase stability and long‐term ambient stability against light, heat, and humidity. This work provides a viable strategy in fabricating high‐performance narrow‐bandgap all‐inorganic PSCs. Abstract : The Sn‐Pb alloyed perovskite films with stable α ‐phase and oxidation resistance are prepared by bulk doping (CsCl) and surface coordination (PbSO4 ). The less oxidation of Sn 2+ and enhanced stability are caused by reconfiguring perovskite crystallization and the formed dense water‐insoluble hydrophobic surface. The ultimately fabricated perovskite solar cells deliver a champion power conversion efficiency of 10.39% and excellent stability.